Who needs migrant workers? labour shortages, immigration, and public policy - Ruhs, Martin; Anderson, Bridget, D. Phil. (Oxford : Oxford University Press, 2010)
This book provides a framework for analysing labour immigration and public policy. It looks at the changing role of migrant workers and the demand for labour across six sectors: health social care, hospitality, food production, construction, and financial services.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Foreign workers -- Great Britain; Foreign workers -- Government policy -- Great Britain; Labor supply -- Great Britain; Labor mobility -- Great Britain